2014
DOI: 10.1186/s40555-014-0074-7
|View full text |Cite
|
Sign up to set email alerts
|

The diaptomid fauna of Israel (Copepoda, Calanoida, Diaptomidae), with notes on the systematics of Arctodiaptomus similis (Baird, 1859) and Arctodiaptomus irregularis Dimentman & Por, 1985 stat. rev

Abstract: Background: To date, only scarce information is available about the diaptomid copepods of the Middle East despite the ecological and biogeographical importance of the family Diaptomidae in the inland waters of the Holarctic region. Moreover, the taxonomic status of some of the taxa occurring in the area is in need of revision. We studied crustaceans collected from temporary and permanent lentic water bodies in Israel with the aim of providing an updated census of the diaptomid copepods occurring in the country… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…2). In addition to the species listed below, Kiefer (1978) and Dussart and Defaye (2002) reported the presence of Arctodiaptomus similis (Baird, 1859) in Sardinia, although no other data were provided by these authors to substantiate the record of this species, which occurs in eastern Europe and the Middle East (Marrone et al, 2014). A review of the correspondence between late prof. E. Stella and prof. F. Kiefer (now deposited in F. Stoch library) led to the finding of an explicit mention of a single female Arctodiaptomus specimen from Sardinia whose morphology and chaetotaxy were compatible with A. similis (File S3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2). In addition to the species listed below, Kiefer (1978) and Dussart and Defaye (2002) reported the presence of Arctodiaptomus similis (Baird, 1859) in Sardinia, although no other data were provided by these authors to substantiate the record of this species, which occurs in eastern Europe and the Middle East (Marrone et al, 2014). A review of the correspondence between late prof. E. Stella and prof. F. Kiefer (now deposited in F. Stoch library) led to the finding of an explicit mention of a single female Arctodiaptomus specimen from Sardinia whose morphology and chaetotaxy were compatible with A. similis (File S3).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the Sicilian populations ascribed to this taxon belong to a putative new species, currently pending a formal description (Marrone et al, 2009;. Other references: Marrone et al, 2013Marrone et al, , 2014Marrone et al, , 2019 Arctodiaptomus (Arctodiaptomus) wierzejskii (Richard, 1888). (WAL), CAP, APU, SAR, COR, SIC.…”
Section: Annotated Checklistmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the genus Phyllodiaptomus has been recorded in Asia, including south China, Turkey, Israel, Uzbekistan, Iran, Iraq, India, Sri Lanka, Nepal, Indonesia, Thailand, Laos, Philippines and Cambodia (Dumont and Ranga Reddy 1993;Dumont et al 1996;Sanoamuang 1999;Sanoamuang and Yindee 2001;Sanoamuang and Teeramaethee 2006;Khalaf 2008;Alekseev et al 2013Alekseev et al , 2016Marrone et al 2014;Bekleyen et al 2017;Guinto et al 2018;Sanoamuang and Watiroyram 2018). Most species are considered endemic to specific countries.…”
Section: Discussionmentioning
confidence: 99%
“…Use of molecular tools for taxonomy might reveal cryptic diversity, especially in case of widespread species like P. blanci, (see Dussart and Defaye, 2002;Marrone et al, 2014), as reported for other taxa (Korn et al, 2013 -Notostraca;Marrone et al, 2010, 2013Schwentner et al, 2013 -Cyclestherida). These findings in relatively large and well-studied Crustacea highlight the potential of discovery of unknown diversity in other groups as well.…”
Section: Mpsementioning
confidence: 87%